2019
DOI: 10.1042/bsr20191103
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA MALAT1 promotes cardiomyocyte apoptosis after myocardial infarction via targeting miR-144-3p

Abstract: Our study aims to excavate the role of metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) in myocardial infarction (MI), especially in an ischemia/reperfusion injury model and the underlying mechanism involving the MALAT1-miR144 axis. Our results demonstrated that the expression of MALAT1 has a higher level, while miR-144 expression significantly reduced in myocardial tissue after MI and also in left anterior descending (LAD)-ligation mice. This result was confirmed in vitro studies in HL-1 cardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 23 publications
1
39
0
Order By: Relevance
“…We observed that miR-144 was highly abundant in MSC-derived exosomes in the present study. Consistent with other findings that miR-144 has antiapoptotic effects on CMCs in hypoxic conditions both in vitro and in vivo [17,35], we have demonstrated that miR-144 contained in MSC-derived exosomes protects CMCs from hypoxic injury by reducing cellapoptosis. MiR-144 mimics and a miR-144 inhibitor were used to further understand the anti-apoptotic functions of miR-144 in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…We observed that miR-144 was highly abundant in MSC-derived exosomes in the present study. Consistent with other findings that miR-144 has antiapoptotic effects on CMCs in hypoxic conditions both in vitro and in vivo [17,35], we have demonstrated that miR-144 contained in MSC-derived exosomes protects CMCs from hypoxic injury by reducing cellapoptosis. MiR-144 mimics and a miR-144 inhibitor were used to further understand the anti-apoptotic functions of miR-144 in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…MALAT1 was increased in serum of AMI and the serum MALAT1 might be used as the biomarker for AMI diagnosis . High expression of MALAT1 and low level of miR‐144 were found in myocardial tissue after myocardial infarction (MI) . And, MALAT1 was also induced by hypoxia and promoted mouse cardiomyocytes apoptosis via targeting miR‐144 .…”
Section: Malat1 and Cardiac Dysfunctionmentioning
confidence: 95%
“…24 And, MALAT1 was also induced by hypoxia and promoted mouse cardiomyocytes apoptosis via targeting miR-144. 24 Similarly, another study also showed that over-expression of MALAT1 promoted the H/R induced apoptosis of cardiomyocytes line HL-1 cell by sponging miR-145a. 21 MiR-145 could target adenovirus E1B-19 kDa-interacting protein 3, which plays a pivotal role in myocardial IR injury.…”
Section: Myocardial Ischemia Injurymentioning
confidence: 98%
See 2 more Smart Citations